Diskriminasi dan Ujaran Kebencian Pada Perempuan Dalam Game Online Mobile Legends Bang-Bang - Kurniawan, Ferry Dwi; Kamajaya, Gede; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
The study, entitled "Discrimination and Hate Speech Against Women in the Online Game Mobile Legends Bang-Bang," aims to analyze and describe the forms and impacts of discrimination and hate speech targeting female players in the online game Mobile Legends Bang-Bang. The analysis uses Pierre Bourdieu's theory of symbolic violence, where this qualitative research involves interviews and observations with selected informants. The research findings reveal that female players face masculine stigma, stereotypes, power limitations, and social exclusion in the gaming community. Hate speech manifests itself through abusive language and insults related to animals through in-game communication. This behavior negatively impacts the psychological, social, and overall participation of women in the world of e-sports. The study concludes that such discrimination and hate speech are not isolated acts, but rather part of a subtle and systemic mechanism of social domination, where language and symbols in the gaming community reinforce male dominance and normalize negative views of women, even by the victims themselves. Keywords: Discrimination, Hate Speech, Women, Symbolic Violence